Size effect of carbon fiber-reinforced silicon carbide composites (C/C-SiC): Part 1 – bending load and statistical effects. Issue 14 (November 2021) - Flauder, Stefan; Langhof, Nico; Krenkel, Walter; Schafföner, Stefan
Highlights: Size effect of flexural strength for C/C-SiC exists. Weibull modulus is not a material constant for C/C-SiC. Weibull modulus depends on load condition and tested volume. Weakest link approach for C/C-SiC highly questionable. Abstract: This study analyzed the influence of the sample volume, number of tested specimen, and testing method on the flexural strength of fabric-reinforced ceramic matrix composites. For this purpose, seven different batches of C/C-SiC were prepared with four different sample thicknesses to determine the flexural strengths and Weibull moduli by three- and four-point flexural tests. The result showed that C/C-SiC exhibits a size effect of strength under bending load because a decrease of measured flexural strength with increased specimen size was observed. This size effect was discussed regarding the Weibull weakest link approach and the concept of quasi-brittle materials.The determined Weibull moduli were comparable for the same load condition but dissimilar for the identical material if the load condition were changed from three- to four-point bending. Hence, the Weibull modulus was found to be not an inherent material constant for C/C-SiC and the Weibull weakest link approach seems not appropriate.